Synthesis and characterization of a new 4-methoxysalicyliden-p- aminoacetophenoneoxime and its complexes with Co(II), Cu(II) and Zn(II) - Tuna, S.; Canpolat, E.; Kaya, M. (My University, 2006)
The novel Schiff base ligand, 4-raethoxysalicyliden-p- aminoacetophenoneoxime (LH) was synthesized starting from p- aminoacetophenoneoxime and 4-methoxysalicylaldehyde. Mononuclear cobalt(II), copper(II) and zinc(II) complexes of the ligand have been prepared by using Co(II), Cu(II) and Zn(II) salt with a metal to ligand ratio of 1:2. The structures of the ligand and its complexes were identified by using elemental analyses, IR, 1H- and 13C-NMR spectra, magnetic susceptibility measurements, UV spectra and thermogravimetric analyses (TGA).
Keywords: Cobalt(II); Copper(II) and zinc(II) complexes of Schiff bases; Schiff bases